The common good and human dignitySome very preliminary remarks - Koopman, Nico (Nederduitse Gereformeerde Teologiese Tydskrif, 2012)
This paper attempts to give a description of the use of the notion of “the common good” in theological discourse. A brief historical analysis of the idea of common good is offered. A distinction is made between so-called thinner and thicker modes of the common good. It is argued that consensus on the thinner and thicker versions of the common good is plausible and possible. Guidelines are offered for dealing with situations where disagreement and incommensurability exist with regard to effectively serving the common good. Suggestions are made for realising the common good, e.g. the formulation and implementation of appropriate policies and practices, as well as the formation of people of virtue and character. In conclusion, three functions of the common good are suggested.